Geodynamic evolution of the African craton West in the North of Ghana - (:unkn) unknown (My University, 2015)
This thesis focuses on the Paleoproterozoic geological evolution of the West African Craton in northern Ghana. New lithological, metamorphic and structural regional maps are built from the interpretation of field and airborne geophysical data. The crust in northern Ghana comprises greenstone belts gneissic terranes, and granitoids. The latter have a calc-alkaline affinity, or are analogue to Archean TTGs, and formed between 2.21 and 2.11 Ga. Lu-Hf isotope analyses show that the magmas are juvenile and derived from a source extracted from the mantle at 2.45-2.30 Ga.The Eburnean metamorphic record of northern Ghana reflects a diversity of thermal regimes. Metamorphic relics record conditions that correspond to a cold apparent geothermal gradient (BT-HP, ~15°C/km). They are overprinted by amphibolite- to high-P granulite-facies metamorphism (MP-MT, 20°C/km) starting at 2145 Ma, followed by another metamorphic phase in the amphibolite facies (25-30°C/km) between 2125 and 2105 Ma. The metamorphic evolution is interpreted to reflect the interplay between crustal thickening and gravitational flow of the orogeny. We suggest that a major magmatic event started at 2.45 Ga and produced fragments of juvenile crust, that formed the protolith of the West African Craton's crust. Northern Ghana may represent a suture zone between two distinct cratonic fragments that collided. Its geological record shares some similarities with modern orogenic belts, although it is not strictly identical. The Paleoproterozoic geodynamic settings may be unique in the history of the Earth, and represent a transitional regime in its secular evolution, between archaic geodynamics and modern plate tectonics.
Keywords: African Research